ҚЫТАЙ ДҮНИЕТАНЫМЫНДАҒЫ ТҮСТЕР - Анипина, А. К. (Journal of Oriental Studies, 2016)
В этой статье рассматриваются все цвета по китай- ской традиций. С древних времен китайский народ уде- лял большое внимание к цветам. Из этой статьи можно узнать об особенностях использования цветов китай- скими народами. This article looks at all the colors in chinese tradition. Since ancient times, Chinese people have paid great attention to the colors. From this article you can learn about the peculiarities of the Chinese people to use colors.